Catalyst-, solvent- and desiccant-free three-component synthesis of novel C-2,N-3 disubstituted thiazolidin-4-ones - Abonia, Rodrigo (2016)
Herein it is provided an efficient, environmentally friendly and one-pot procedure for the synthesis of a library of new and diversely substituted 1,3-thiazolidin-4-ones in short reaction times and good yields through a solvent-, catalyst- and desiccant-free three-component process. Reactions proceeded by treatment of primary benzyl(aryl)amines with aromatic aldehydes (and ketones) and 2-mercaptoacetic acid acting as both reagent and self-catalyst. All reactions were performed in sand bath instead of the commonly used oil bath avoiding the generation of undesired volatile materials proceeding of the thermal decomposition of the oils. IR, Mass and NMR experiments as well as X-ray diffraction confirmed structures of the obtained products.